1495. Incidence of Sexually Transmitted Infections (STIs) in Patients on Pre-exposure Prophylaxis (PrEP). (26th November 2018) - Hamed, Almutase; Saling, Christopher; Brown, Melinda S; Szabela, Maria Elaine; Jayasingam, Rajasingam; Siegal, Arthur; Slim, Jihad
Abstract: Background: Pre-exposure prophylaxis (PrEP) is a highly effective method for preventing HIV transmission among at-risk patients. There is limited and conflicting data regarding the risk of other STIs following PrEP initiation. The objective of this study was to compare the incidence of STIs before and during PrEP therapy. Methods: A retrospective observational study of patients seeking PrEP therapy at an inner-city clinic in Newark, New Jersey, between May 1, 2016 and March 30, 2018. Patients who were MSM, intravenous drug users, or heterosexual with multiple or HIV-positive partners were considered at risk for HIV and offered PrEP. Patients were initially screened and tested every 3 months for HIV, Chlamydia trachomatis, Neisseria gonorrhoea, syphilis, hepatitis B virus (HBV), hepatitis C virus (HCV), hepatitis A virus (HAV), herpes simplex virus (HSV), medication adherence and continued high-risk behavior. Patients were also counseled on risk-reduction behaviors. STI incidence before and during PrEP was compared. Results: Between May 1, 2016 to March 30, 2018, 125 patients were considered at risk. Fifty-one (41%) patients were lost to follow-up after the initial visit and were excluded. Seventy-four (59%) patients completed screening and were included in the study. The mean age was 35.0 ± 11.6 years. The majority of the patients were males 74% (54). 29 (40%) were MSM, and 33 (45%) had HIV-positive partners. The mean duration of PrEP was 386 ± 183 days. Upon initial screening 14 (19%) patients were positive for at least one STI; 3 (21%) patients had HCV, 3 (21%) had chlamydia, 2 (14.3%) had HBV, 2 (14.3%) had gonorrhea, 2(14.3%) had syphilis, one had HSV II and one was found to have HIV. Two patients acquired a new STI on PreP. One tested positive for chlamydia and gonorrhea 1 month after initiating prep and another contracted syphilis after 6 months. No patient had recurrent STIs nor acquired HIV while on PrEP therapy. Conclusion: The use of PrEP not only reduces the transmission of HIV but also appears to reduce the incidence of other STIs. Frequent STI screenings and behavioral counseling on risk reduction likely contributed toward lower STI incidence. Larger studies examining similar data over longer durations are needed to confirm these findings. Disclosures: All authors: No reported disclosures.